2001
DOI: 10.1515/jpem.2001.14.5.459
|View full text |Cite
|
Sign up to set email alerts
|

Update on Endocrine Disturbances in Anorexia Nervosa

Abstract: The marked endocrine changes that occur in anorexia nervosa have aroused a great deal of interest, and over the last decade much research has been conducted in this field. The endocrine disturbances are not specific to this disorder, as they also occur in starvation states secondary to other causes, and they return to normal upon weight restoration. However, emaciation may have profound effects on psychological processes, establishing an intricate circular interaction whereby somatic and psychological manifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 222 publications
1
35
0
Order By: Relevance
“…It is known that the growth hormone (GH) exerts a marked trophic effect on intestinal mucosa, likely through the action of the insulin-like growth factor-I (IGF-I). 20 Anorexic patients, in spite of an increased production of GH, have very reduced IGF-I levels, 21 which prevents the GH from exerting its biological effects. Therefore, it is plausible that the IGF-I deficiency may account for changes of IP observed in our anorexic patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the growth hormone (GH) exerts a marked trophic effect on intestinal mucosa, likely through the action of the insulin-like growth factor-I (IGF-I). 20 Anorexic patients, in spite of an increased production of GH, have very reduced IGF-I levels, 21 which prevents the GH from exerting its biological effects. Therefore, it is plausible that the IGF-I deficiency may account for changes of IP observed in our anorexic patients.…”
Section: Discussionmentioning
confidence: 99%
“…2). Reliable data are not available to establish the percentage of growth lost in these patients, with the exception of one study where it was estimated that 3 cm is lost in some patients in relationship to their target height (40).…”
Section: Hypothalamic -Pituitary-ovarian Axismentioning
confidence: 99%
“…Stoving et al (83) determined thyroid volume by ultrasonographic methods in patients with AN and demonstrated that this gland is markedly reduced in comparison with age-and sex-matched controls. This thyroid atrophy is not due to low TSH levels, as TSH levels are usually normal in AN.…”
Section: Hypothalamic -Pituitary -Thyroid Axismentioning
confidence: 99%
See 1 more Smart Citation
“…It may result during illness, after stress exposure, or as a response to homeostatic challenges such as cellular dehydration (Siegfried et al, 2003). In contrast to food restricted or dieting individuals, anorexic patients present normal or subnormal serum levels of T 4 and TSH (Stoving et al, 2001); also, a blunted TSH release form the pituitary after TRH administration (Tamai et al, 1986). Alterations of the HPT axis in anorexia nervosa have most likely a central origin, due to the reduced hypothalamic TRH secretion, and resemble those of the NTIS.…”
Section: Dehydration-induced Anorexiamentioning
confidence: 99%